1996
DOI: 10.1159/000244352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cordocentesis on Inferior Vena cava Velocity Waveforms: Differences between Normally Grown and Growth-Retarded Fetuses

Abstract: The objective of this study was to analyze the effects of cordocentesis on velocity waveforms recorded from the inferior vena cava and to evaluate differences, if any, in the hemodynamic response between normally grown and growth-retarded fetuses. Twenty-five normally grown fetuses and 20 growth-retarded fetuses were considered for this study. This latter group was characterized by abnormal Doppler indices in the umbilical artery and the middle cerebral artery suggestive of uteroplacental insufficiency as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Currently, assessment of fetal cardiac function with Tei index has been evaluated in various conditions such as after laser therapy in twin‐to‐twin transfusion syndrome, fetuses with hemoglobin Bart's disease and fetuses with severe growth‐restriction . Although some studies have reported the effect of cordocentesis on cardiotocography and inferior vena cava waveform, to date, the effect of cordocentesis on fetal Tei index had not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, assessment of fetal cardiac function with Tei index has been evaluated in various conditions such as after laser therapy in twin‐to‐twin transfusion syndrome, fetuses with hemoglobin Bart's disease and fetuses with severe growth‐restriction . Although some studies have reported the effect of cordocentesis on cardiotocography and inferior vena cava waveform, to date, the effect of cordocentesis on fetal Tei index had not been evaluated.…”
Section: Discussionmentioning
confidence: 99%